A Comparison between the Effectiveness of computerized Cognitive Rehabilitation Training and transcranial Direct Current Stimulation on Dialysis Patients’ Executive Functions - Fatemeh Firouzan; Vahid Sadeghi-Firoozabadi; Vahid Nejati; Jalil Fathabadi; Ahmad Firouzan (Health Psychology Research)
# Purpose